2010
DOI: 10.1108/00368791011012425
|View full text |Cite
|
Sign up to set email alerts
|

Lubricating behavior of tripod sliding universal joints

Abstract: Purpose -The purpose of this paper is to understand the lubricating properties of the tripod sliding universal joint (TSUJ) in order to overcome its premature failures caused by the poor lubricating regime. Design/methodology/approach -A simplified geometrical model is derived from the main mating surfaces redesigned, and then the effects of the applied load and reduced elastic modulus, as well as the lubricant viscosity on the pressure and film thickness, are theoretically studied by using multilevel methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Some researchers have studied the lubricating properties of the TSUC. Wang and Chang (2009, 2010) analyzed the effects of various factors on the film thickness and the pressure distribution of the oil lubricating. Chang et al (2010) investigated the effect of effective radius on oil lubricating properties considering the thermal effect.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have studied the lubricating properties of the TSUC. Wang and Chang (2009, 2010) analyzed the effects of various factors on the film thickness and the pressure distribution of the oil lubricating. Chang et al (2010) investigated the effect of effective radius on oil lubricating properties considering the thermal effect.…”
Section: Introductionmentioning
confidence: 99%
“…The effects affect oil film thickness and pressure distributions in the tripod sliding universal joint have been analyzed by Chang (2009, Wang et al (2014). Wang and Chang (2010) investigated the effects of reduced elastic modulus, applied load and lubricant viscosity on the oil film thickness and pressure distributions. Chang et al (2010) presented the oil lubricating properties of TSUCs considering thermal effect.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous investigation of TSUJ, Chang (2009b, 2010) and Chang et al (2010) observed its lubricating performance by using the simplified geometric model (Wang and Chang, 2010) shown in Figure 3 under isothermal Newtonian flow conditions and then further studied the effect of the effective radius on the lubricating behavior thereof considering thermal effect. In this work, the lubricating properties of the TSUJ were also investigated by using the simplified geometric model shown in Figure 3 under thermal Newtonian flow condition.…”
Section: Introductionmentioning
confidence: 99%